Study of Al-Qur'an Tahfizh Learning Methods in Pattani Southern Thailand - Miss Nurfaseera Hawaesoh (SYAMIL: Journal of Islamic Education, 2022)
The presence of education and efforts to memorize the Al-Qur'an in Islamic boarding schools departs from the concerns of religious leaders and the government regarding the ability of the younger generation of Muslims and Muslims in general to read and understand the holy book of the Al-Qur'an and its application in everyday life. relatively low. Al-Qur'an tahfiz education which has been carried out by various Islamic study institutions, both within the scope of Islamic boarding schools and public schools, generally contributes to the improvement of students' learning achievement. Not only that, tahfiz Al-Qur'an can also form an optimistic attitude, and the noble character of tahfiz Al-Qur'an education can be realized. This study uses a qualitative descriptive approach, where descriptive research is not intended to test certain hypotheses, but only describes a variable, symptom, or situation. The type of research used is field research. The data collection technique used in this study is direct observation. As for the location of the research, namely in Islamic boarding schools which hold a program of memorizing the Koran as the main program. Research results describe that Tahfiz education in Thailand is still very minimal. This is because the focus of Islamic Education is only on aspects of formal Education. Islamic institutions in Thailand, especially tahfiz education, use various rote methods developed by the Institute from several methods that apply in Indonesia. Of course, this method needs time to be adapted by the tahfiz educational institution in Thaliand. Islamic Education Institutions, especially tahfiz, which have had a positive impact for a long time, this can be seen from the many alumni who have hafiz at the Institute by using the rote method according to the character of the students.